A new stiffness evaluation toward high speed cell sorter - Hirose, Yuki; Tadakuma, Kenjiro; Higashimori, Mitsuru; Arai, Tatsuo; Kaneko, Makoto; Iitsuka, Ryo; Yamanishi, Yoko; Arai, Fumihito (2010 IEEE International Conference on Robotics and Automation, 2010)
Cell stiffness could be an index for evaluating its activity. Although various systems measuring cell stiffness have been proposed so far, they are slow for adaptively connecting to cell sorters capable of handling more than 1000 [cells/sec]. This paper proposes a new approach that can indirectly evaluate the cell stiffness by measuring the passing time for a narrow channel. When a cell passes through the channel, it receives a viscous force depending upon how much deformation is exerted on the cell. We show that the stiffness is a function of both the passing time and the initial diameter of cell. We also show that the stiffness is proportional to the passing time and inversely proportional to the initial diameter, under the assumption that the thickness of fluid film is inversely proportional to the normal force. The experimental validation is given together with the basic working principle.